No association of CDK5 genetic variants with Alzheimer's disease risk - Combarros Onofre; Berciano José; Infante Jon; Rodríguez-Rodríguez Eloy; Sánchez-Juan Pascual; Mateo Ignacio; Vázquez-Higuera José (BMC, 2009)
Abstract Background As cyclin-dependent kinase 5 (CDK5) has been implicated in the abnormal hyperphosphorylation of tau in Alzheimer's disease (AD) brain, and the development of neurofibrillary tangles, we examined the contribution of this gene to the susceptibility for AD. Methods We examined genetic variations of CDK5 by genotyping haplotype tagging SNPs (htSNPs) (rs9278, rs2069459, rs891507, rs2069454, rs1549759 and rs2069442) in a group of 408 Spanish AD cases and 444 controls. Results There were no differences in the genotypic, allelic or haplotypic distributions between cases and controls in the overall analysis or after stratification by APOE ε4 allele. Conclusion Our negative findings in the Spanish population argue against the hypothesis that CDK5 genetic variations are causally related to AD risk. Still, additional studies using different sets of patients and control subjects deserve further attention, since supporting evidence for association between CDK5 gene and AD risk in the Dutch population exists.